Предмет: Алгебра,
автор: kseniadanilova
(х+1)³-х²*(х+3)+2=0
Помогите прошу!!!
Ответы
Автор ответа:
1
( a + b )³ = a³ + 3a² b + 3ab² + b³
( x + 1 )³ = x³ + 3x² + 3x+ 1
(x³ + 3x² + 3x+ 1) - x³ - 3x² + 2 = 0
3x+ 1 + 2 = 0
3x + 3 = 0
3x = - 3
x = - 3/3 = - 1
( x + 1 )³ = x³ + 3x² + 3x+ 1
(x³ + 3x² + 3x+ 1) - x³ - 3x² + 2 = 0
3x+ 1 + 2 = 0
3x + 3 = 0
3x = - 3
x = - 3/3 = - 1
Автор ответа:
1
(x+1)^3-x^(x+3)+2=0
x^3+3x^+3x+1-x^3-3x^+2=0
3x+3=0
3x=-3
x=-3/3
x=-1
x^3+3x^+3x+1-x^3-3x^+2=0
3x+3=0
3x=-3
x=-3/3
x=-1
Похожие вопросы
Предмет: Английский язык,
автор: arinawolt55
Предмет: Русский язык,
автор: катя200646
Предмет: Английский язык,
автор: Sarah2004
Предмет: Математика,
автор: Аноним
Предмет: Русский язык,
автор: карина2369